Assessment of utilization of maternal health care services in rural field practice areas of VIMS, Ballari - N., Neeta P.; A. R. B., Sameena; C. M., Suresh; Goud, Gangadhar; ., Bharat; Sajjan, Saraswati; ., Chetana (International Journal Of Community Medicine And Public Health, 2017)
Background: Maternal mortality and morbidity remains high even though national programs exist for improving maternal and child health in India. This could be related to several factors, an important one being non-utilization or delay in seeking care of maternal health-care services, especially amongst the rural poor and urban slum population due to either lack of awareness or access to health-care services. Our study was aimed to know the utilization of maternal health care services during antenatal and post natal period and factors affecting them. Methods: A Community based cross sectional study was carried in the rural field practice areas of VIMS, Ballari (three primary health centres (PHC) Kudithini, Koluru, Kurugodu) among all married women in the age group of 15-45 years who were in the post natal period (less than 2 months) at time of interview. A total 152 women were included in the study by door to door survey, among all the 3 PHC’s. The women absent during the survey were excluded. Results: Only 101 (66.44%) of women utilized antenatal care and 18 (11.8%) utilized post natal care (at least three postnatal visits) from the health care facility. Mothers who were of Muslim religion, <20 years of age, higher education of participant as well as husband, higher occupation status, high SES, less parity had higher odds of utilizing antenatal care. Health education by the health worker regarding post natal services to women ranged from 62.5-90.8%. Mothers of Muslim religion, higher education, higher occupation status, normal vaginal delivery and home delivery had higher odds of utilizing postnatal services Conclusions: The study shows unacceptably low utilization of postnatal care services. It shows the coverage of postnatal care services is inadequate. This is an important message to health service providers and policy makers to strengthening not only antenatal health services and institutional deliveries but also postnatal care services to reduce maternal and neonatal morbidity and mortality.